Oil Emulsion Separation Using Forward Osmosis And Its Performance Evaluation - Kunalan, Melvin Raj (Universiti Sains Malaysia, 2018)
In this study, the separation of water from synthetic produced water and oil-in-water emulsion via forward osmosis was carried out. The membrane used in this study was thin film composite (TFC) membrane with an active polyamide layer. The effect of different feed oil concentrations (50ppm, 100pp, and 500ppm) on the membrane performance was studied. It was found that the water permeate flux decreased when the feed oil concentration was increased due to the formation of cake layer on the membrane surface. The permeate flux of oil-in-water emulsion is higher than that of synthetic produced water due to the presence of sea salt in the synthetic produced water that gives a higher osmotic pressure. The fouling phenomena of the membrane is observed and analysed using scanning electron microscope (SEM). The TFC membranes used in this study gave an effective oil rejection rate of 99.2% with minimal fouling tendency. The flux values obtained for synthetic produced water and oil-in-water emulsion were 0.001295 m3/m2.h and 0.004078 m3/m2.h respectively.